The effect of product aesthetics information on website appeal in online shopping. Issue 2 (5th June 2017) - Peng, Xianghui; Peak, Daniel; Prybutok, Victor; Xu, Chenyan
Abstract : Purpose: This research posits that e-vendors can use product aesthetic information (PAI) as a strategic positing tool to shape consumers' perceptions of e-vendors' websites. Design/methodology/approach: To test this framework, variations on a garment's color (a crucial element of product aesthetics) are presented to four different treatment groups to determine whether aesthetic treatment influences the perception of the website. Findings: The results suggest that consumers who consider a product visually appealing also perceive the e-vendor's website as useful, resulting in enjoyment of the shopping experience. Positive perceptions lead consumers to form positive attitudes toward the vendor's website. Originality/value: While product aesthetics is well-studied in marketing and psychology, its relevance to the e-commerce domain is relatively underexplored. To fill the void, the paper proposes a theoretical framework that explains how PAI influences buyers' cognitive and affective evaluations of their online shopping experiences, which in turn shapes their attitudes toward e-vendors' sites.